2016
DOI: 10.1039/c5cp07442h
|View full text |Cite
|
Sign up to set email alerts
|

Proton transfer aiding phase transitions in oxalic acid dihydrate under pressure

Abstract: Oxalic acid dihydrate, an important molecular solid in crystal chemistry, ecology and physiology, has been studied for nearly 100 years now. The most debated issues regarding its proton dynamics have arisen due to an unusually short hydrogen bond between the acid and water molecules. Using combined in situ spectroscopic studies and first-principles simulations at high pressures, we show that the structural modification associated with this hydrogen bond is much more significant than ever assumed. Initially, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 90 publications
(110 reference statements)
0
23
0
Order By: Relevance
“…The rate of decrease of the νOH band can be interpreted as a proxy for the strength of the bond, suggesting that all of the constituent components of the sporopollenin undergo greater changes under pressure than the natural material. Of those studied, only p ‐coumaric acid and sebacic acid show signs of new hydrogen bonding within pure samples.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of decrease of the νOH band can be interpreted as a proxy for the strength of the bond, suggesting that all of the constituent components of the sporopollenin undergo greater changes under pressure than the natural material. Of those studied, only p ‐coumaric acid and sebacic acid show signs of new hydrogen bonding within pure samples.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the calculated value, we plot the bond length of N-H and O-H changes as a function of pressure in Figure S5 (Supporting Information), It can be seen that the proton transfer from SQ to BP occurs at about 1.5 GPa suggests that the double proton transfer structure possess the lowest enthalpy under compression, and the first-order phase transition can be associate with the proton transfer 59 . For BP molecule, the two pyridine rings are not coplanar and form a dihedral angle of 34◦ at ambient condition, the calculated dihedral angle decreases with increasing pressure (shown in Figure S6 (Supporting Information)), which is similar to the structural change of BP at high temperature 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The proton acceptor-BP possesses a non-planar aromatic molecular geometry under ambient conditions. It has been reported that the intensity ratio between ring breathing and C-C stretching mode can correlate with the dihedral angle between two pyridine ring in BP 6467 . The smaller dihedral angle is, the lower intensity ratio of ring breathing to C-C stretching mode is.…”
Section: Resultsmentioning
confidence: 99%
“…Compound Probe (Casati et al, 2009), as well as by IR spectroscopic methods (Bhatt et al, 2016). As for NÁ Á ÁHÁ Á ÁO hydrogen bonds, there are indications that a similar proton transfer provoked by exerted pressure takes place in the 1:1 adduct of squaric acid and 4,4 0 -bipyridine (Martins et al, 2009).…”
Section: Referencementioning
confidence: 89%